TO COMPARE THE EFFECTIVENESS OF NIFEDIPINE AND GLYCERYL TRINITRATE PATCH IN PREVENTION OF PRETERM LABOUR - Yasmin, Sumaira; Sabir, Samina; Zahoor, Farnaz (Journal of Postgraduate Medical Institute, 2016)
Objective: To assess the effectiveness of Nifedipine and Glyceryl trinitrate patch in prolonging the pregnancy for more than 48 hours. Methodology: This was a randomized control study. Fifty patients with preterm labour meeting the inclusion criteria were inducted in study and ran-domly allocated to the treatment group A (Nifedipine) and group B (Glyceryl trinitrate patch, GTN). After taking consent from the patients, all the details were documented on a proforma and tocolysis was started with either of these tocolytics according to a preset protocol. Results: Nifedipine was found to be more effective than GTN, as prolongation of pregnancy beyond 48 hours was more frequent (74 %) with nifedipine than GTN (40%) with P value <0.05 . Similarly prolongation beyond 7 days was also more frequent (32%) with nifedipine as compared with GTN (24%). Most com-mon adverse effect found with nifedipine was headache followed by palpita-tions and hypotension. GTN patch had a better side effect profile with most of the patients being asymptomatic. Fetal distress was noticed more in GTN group as compared with nifedipine. Conclusion: Nifedipine, as a tocolytic, is found to be more effective in preg-nancy prolongation when compared with Glyceryl trinitrate but has frequent maternal adverse drug effects. Glyceryl trinitrate patch is well tolerated by the patients with preterm labour with relatively fewer side effects.